Odpowiedzi

Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-02-07T18:19:06+01:00
A) 6(x-4)-2=6x-24-2=6x-26

b) 2(x+1)-3(x-1)=2x+2-3x+3=-x+5
c) -3(y-2)+4(y+2)=-3y+6+4y+8=y+14
d) 5(x-y-1)-4(x+2)=5x-5y-5-4x-8=x-5y-13
e) 2(3a+b)-2(a-b)=6a+2b-2a+2b=4a+4b
f) jedna druga (4x-4)-2x=2x-2-2x=-2

g) x(x-1)-3(x do kwadratu -x)=x²-x-3x²-3x=-2x²-4x
h)5a (a-3)-3a(a-5)=5a²-15a-3a²+15a=2a²
i) 3x(x+jedna trzecia y)-2y(jedna druga x - jedna druga)=3x²+y-yx-y=3x²+yx
3 4 3
2010-02-07T18:20:12+01:00
A) 6(x-4)-2 = 6x-20-2=6x-22
b) 2(x+1)-3(x-1) = 2x+2-3x+3=x+5
c) -3(y-2)+4(y+2) = -3y+6+4y+8=y+14
d) 5(x-y-1)-4(x+2) = 5x-5y-5-4x-8=x-5y-13
e) 2(3a+b)-2(a-b)= 6a+2b-2a+2b=4a
f) jedna druga (4x-4)-2x = 2x-2-2x=-2
g) x(x-1)-3(x do kwadratu -x) = x²-x-3x²+3x=-4x²+2x
h)5a (a-3)-3a(a-5)= 5a²-15a-3a²+15=2a²
i) 3x(x+jedna trzecia y)-2y(jedna druga x - jedna druga) =3x²+xy-xy+x=3x²+x
11 4 11